Freakboy - Clark, Kristin Elizabeth (Farrar Straus Giroux, 2013)
Told from three viewpoints, seventeen-year-old Brendan, a wrestler, struggles to come to terms with his place on the transgender spectrum while Vanessa, the girl he loves, and Angel, a transgender acquaintance, try to help